2012
DOI: 10.1177/0021934712463237
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Conflicts . . . Strengths and Supports

Abstract: Most studies of marriage among African Americans have adhered to a problem-oriented perspective. Consequently, relatively little is known about enduring African American marriages. As marriage confers numerous psychosocial and economic benefits, there is merit in studying the characteristics of African American marriages that stand the test of time. Seventy-one married African American couples (mean length of marriage = 32 years) provided information regarding their religious practices, perceived reasons for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Qualitative work on enduring Black marriages points to both of these truths. Married Black couples often discuss the unique challenges and strains of Black family life, including racial discrimination, but also report turning to and relying heavily on their spouse to overcome such challenges (Marks et al, 2008; Phill, Wilmoth, & Marks, 2012). Importantly, the average length of marriage for our sample of Black couples was 32 years and over 90% had been married for at least 10 years (data not shown in tables).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative work on enduring Black marriages points to both of these truths. Married Black couples often discuss the unique challenges and strains of Black family life, including racial discrimination, but also report turning to and relying heavily on their spouse to overcome such challenges (Marks et al, 2008; Phill, Wilmoth, & Marks, 2012). Importantly, the average length of marriage for our sample of Black couples was 32 years and over 90% had been married for at least 10 years (data not shown in tables).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, a previous study (Melgosa, 2004) reported that men and women communicate differently; women desire mutual acceptance and share more of their emotions during conversations with their spouse, whereas men have limited emotions, desire to 'win' in their conversations, and want their spouse to accept this. Lack of proper communication has been reported to cause marital constraints (Phillips, 2012). Interruptions, ignoring a spouse's concerns, unfinished talk on the same matter (even after apologies), or silence may be interpreted as a lack of respect for the spouse's concerns and escalate into conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Brody, Stoneman, Flor, and McCrary (1994) found that religiosity was related to better quality marital interaction and lower levels of marital conflict. Similarly, studies of African Americans in long-lasting marriages have identified religion as a major resource for the couples (Carolan & Allen, 1999; Marks et al, 2008), and 93% of husbands and 94% of wives reported that their faith was a “very important” factor in their marital longevity (Phillips, Wilmoth, & Marks, 2012). Brown et al (2008) also found that religiosity predicted marital stability over time, but only when assessed by service attendance and only for wives.…”
Section: Religion Spirituality and Marital Qualitymentioning
confidence: 99%